RAINFALL INTERCEPTION IN PINUS TAEDA L. PLANTATION IN SOUTHERN BRAZIL - Lange, Daniel Ribeiro; Santos, Irani dos (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
The Santa Catarina plateau has undergone significant changes in the landscape in recent decades after the introduction of pine plantations, potentially altering the hydrological balance – though there are few local studies on this subject. In this context, this research aimed to evaluate the effects of the development of Pinus taeda L. plantations (with ages of 5, 7 and 10) on the interception process through hydrological monitoring. To quantify the components of the interception process, this study measured the external rainfall, throughfall and stemflow in Pinus taeda L. plantations in the municipality of Rio Negrinho (SC). The interception components were monitored in 54 events between September 2017 and January 2019. In addition, dendrometric parameters – such as vegetation density, diameter at breast height (DBH), cover index (C) and leaf area index (LAI) – were measured as a way to characterize the representative vegetation in each site. During the study period, the average throughfall rates (Tf) were 74%, 58% and 65%, and the stemflow rates (Sf) were 6.8%, 9.7% and 12.7% for the ages of 5, 7, 10 years, with densities of 1,333 (ha-¹), 1,100 (ha-¹) and 1,666 (ha-¹), respectively. These results indicate that, in homogenous stands of Pinus taeda L., the increase in age is not directly related to the reduction of the Tf rate. This presents a better relation to the spacing patterns of the forests and the consequent alteration of the environmental characteristics that determine its development.